Effect of Ball Milling and Annealing on the Formation of Nano-Y4Ni3O10 - A. El-Meligi, A.; Bououdina, M.; M. Al-Saie, A. (Recent Patents on Materials Science, 2016)
Background: Rare earth elements (Re), nickel and oxygen could form a series of compounds with the general formula Ren+1NinO3n+1 whose structures are described by stacking along the c-axis of n finite LaNiO3 pervoskite layers separated by ReO rock salt like layers. Objective: This study aims at synthesing Y4Ni3O10 (YNO) by ball milling and annealing procedures using oxides of rare earth element, yttrium (Y) and transition metal, nickel (Ni) oxides as a precursor. Methods: X-Ray Diffraction (XRD) is used to investigate samples and magnetic measurements were conducted using a vibrating sample magnetometer. Results and Conclusion: The XRD exhibits that there is no significant formation of the compound Y4Ni3O10 under lower speed of the mill (about 300 rpm). The Y4Ni3O10 compound is partially formed by increasing the mill speed to 500 rpm. There are a number of significant peaks that have been observed in the XRD patterns. The annealed samples without milling up to 1200°C have no effect on the formation of the specified compound. Y4Ni3O10 compound has formed with annealing and high speed of mill. Milling and annealing have a significant effect on the crystallite size of the materials. The crystallite size of phases is varied within nano-range. Magnetic properties of oxide mixture, milled and annealed, which form the Y4Ni3O10 compound, were studied by means of a vibrating sample magnetometer. Annealed samples show low magnetization. The saturation magnetization increases with milling. There are a number of patents invented using rare earth metals, and used in many applications, such as magnets, coats, and biomedical devices.
Keywords: ball milling